The journey is just as important as the destination-Digital neuropsychological assessment provides performance stability measures in patients with acquired brain injury. - Lauriane A Spreij; Isabel K Gosselt; Johanna M A Visser-Meily; Alex J Hoogerbrugge; Timo M Kootstra; Tanja C W Nijboer (PLoS ONE)
Background Cognitive performances on neuropsychological paper-and-pencil tests are generally evaluated quantitatively by examining a final score (e.g., total duration). Digital tests allow for a quantitative evaluation of "how" a patient attained a final score, which opens the possibility to assess more subtle cognitive impairment even when final scores are evaluated as normal. We assessed performance stability (i.e., the number of fluctuations in test performance) to investigate (1) differences in performance stability between patients with acquired brain injury (ABI) and healthy controls; (2) the added value of performance stability measures in patients with ABI; and (3) the relation between performance stability and cognitive complaints in daily life in patients with ABI. Methods We administered three digital neuropsychological tests (Rey Auditory Verbal Learning Test, Trail Making Test, Stroop Colour and Word Test) and the Cognitive Complaints-Participation (CoCo-P) inventory in patients with ABI (n = 161) and healthy controls (n = 91). Results Patients with ABI fluctuated more in their performance on all tests, when compared to healthy controls. Furthermore, 4-15% of patients who performed inside normal range on the conventional final scores were outside normal range on the performance stability measures. The performance stability measures, nor the conventional final scores, were associated with cognitive complaints in daily life. Conclusions Stability in test performance of patients was clearly dissociable from healthy controls, and may assess additional cognitive weaknesses which might not be observed or objectified with paper-and-pencil tests. More research is needed for developing measures better associated with cognitive complaints.